Financial dependence, formal credit, and informal jobs: new evidence from Brazilian household data - Luis A. V. Cat\~ao; Carmen Pagés; Maria Fernanda Rosales (Institute for the Study of Labor (IZA), 2009)
This paper examines a much overlooked link between credit markets and formalization: since access to bank credit typically requires compliance with tax and employment legislation, firms are more likely to incur such formalization costs once bank credit is more widely available at lower cost; if so, well-functioning credit markets help foster formal employment at the expense of informal jobs. We gauge the relevance of this credit channel using the Rajan-Zingales measure of financial dependence and a difference-in-differences approach applied to household survey data from Brazil - a large emerging market where substantial changes in banking system depth and formalization ratios have taken place and for which consistent data exists. Our results show that formalization rates increase with financial deepening and the more so in sectors where firms are typically more dependent on external finance. We also decompose shifts in aggregate formalization into those within each firm size category and those associated with changes in firm size, and find that financial deepening significantly explains the former but not so much the latter.
Keywords: E26; G21; O4; O16; 330; Credit markets; financial dependence; informality; Brazil; Kreditmarkt; Kreditgeschäft; Finanzierung; Informeller Sektor; Schattenwirtschaft; Legalisierung; Brasilien